Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Origin of fast backward steps and detachment of kinesin motor under backward load - Jie Wang; Xiao-Xuan Shi; Yu-Ru Liu; Peng-Ye Wang; Ping Xie (Journal of Theoretical Biology, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Recyclable epoxy vitrimers based on multimechanism-activated transesterification strategies for photothermal conversion and self-healing materials - Huanyu Xu; Liangyi Xing; Ru Wang; Guiyu Chu; Yanmeng Peng; Zhiyue Zhao; Fengjiao Jiang; Shuhua Qi; Hongxia Yan (Chemical Engineering Journal, 2026)

Analyzing phosphorus flow in crop production via interpretable machine learning: Insights from a typical agricultural region of Jiangxi Province, China - Yuejin Chen; Wending Huang; Lele Ru; Shuhui Peng; Wuhu Guo; Evgeny Abakumov; Ekaterina Chebykina; Yalan Zhang; Zanxu Chen; Dan Wang; Shijie Dai; Yanqi Liu; et al. (Applied Geochemistry, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “Hydrological seasonality mediates scale-dependent land use effects on riverine microplastic pollution” [Water Research 301 (2026) 126043] - Qinwei Chen; Peng Wang; Ru Liu; Wang Shu; Guangpeng Liu; Lixin Zhu (Water Research, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Construction of Brick-Wall-Like Topological Olefin-Linked Covalent Organic Frameworks via a Steric-Hindrance-Mediated Strategy for Efficient Uranium Capture - Cheng-Peng Niu; Rui Zhang; Zhi-Hai Peng; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Hydrological seasonality mediates scale-dependent land use effects on riverine microplastic pollution - Qinwei Chen; Peng Wang; Ru Liu; Wang Shu; Guangpeng Liu; Lixin Zhu (Water Research, 2026)

A multi-strategy incorporated artificial bee colony algorithm for multi-AGV scheduling with downtime failure - Maodi Ru; Peng Duan; Yao Cheng; Wenqiang Zou; Kaizhou Gao (Journal of Cleaner Production, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Mobility heterogeneity influences the relationship between built environment and metro travel emissions - Jing Pu; Chen Cai; Wei Zhu; Quan Yuan; Ru Guo; Xingyu Ding; Jia Liu; Kaiming Peng; Yanei Xue; Xiangfeng Huang (Transportation Research Part D: Transport and Environment, 2026)

A capillarity-engineered trilayer Janus pad-based food preservation system for directional exudate management and sustained oregano-oil delivery - Ru Li; Wanru Jin; Lin Wang; Lingling He; Xiaowei Li; Peng Wang (Chemical Engineering Journal, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Polyhydroxypregnane glycosides and deoxyoligosaccharides from Cynanchum acutum subsp. sibiricum and anticomplementary activity of its compounds - Miao-Miao Li; Xue-Ru Wang; Wen-Jing Li; Zhi-Peng Zheng; Yan Lu; Qi Wang (Natural Product Research, 2026)

Calcium chloride inhibits water-soaking disorder of fresh-cut cantaloupe through regulating sugar, organic acid, and anaerobic respiration metabolisms - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Assessing synergy of CO2 and pollutant reductions in industrial parks from the industrial chain perspective - Shenghua Yan; Chen Cai; Jia Liu; Kaiming Peng; Ru Guo; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Novel Lactobacillus Strains Alleviate E. coli-induced Inflammation in a Urinary Tract Infection Rat Model - Sini Kang; Zhihua Peng; Ru Wei; Jiaxin Liu; Hee-Jun Kim; Yongjun Lee; Moonjin Ra; Eun Ji Kim; Heo Keon; Jong Ik Jeon; Min Ji Jang; Myeong Soo Park; et al. (Probiotics and Antimicrobial Proteins, 2026)

A cyclic nucleotide-gated channel gene HcCNGC11 positively regulates salt stress responses in kenaf (Hibiscus cannabinus L.) - Jiao Yue; Canni Chen; Qiuping Wang; Rehmat Ullah; Yuqi Tan; Xu Wang; Huaming Lu; Dengjie Luo; Ru Li; Tao Chen; Peng Chen (Plant Molecular Biology, 2026)

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

Transcriptomic reveals the acute exposure of ammonia nitrogen on muscle quality in fish: the coupling effect of acidity, thermal, and salinity - Ling Peng; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Qiling Huang; Soottawat Benjakul; Dan Jia (Aquaculture, 2026)

Causal-informed domain adaptation with cross-attention for predicting anomalous effluent quality fluctuations in wastewater treatment plants - Hanxin Zhang; Haiping Zhang; Jia Liu; Kaiming Peng; Ru Guo; Feiyun Sun; Xiangfeng Huang; Chen Cai (Water Research, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

LC-MS-based non-targeted metabolomics analysis of sea urchin during frozen storage under different packaging methods - Jia-bo Huang; Yi-hui Tang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Chemistry, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

DcCAMTA6-DcCML8 promotes GABA accumulation in fresh-cut carrots via transcriptional activation of polyamine metabolism genes - Jinglin Zhang; Wanli You; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Sand flux patterns derived from static morphology and migration behavior of barchan dunes in the Taklamakan Desert - Yuan Wang; Peng Liang; Xiaoping Yang; Jiwei Wu; Tinglin Ru; Zihan Wu (Geomorphology, 2026)

A non-specific lipid transfer protein gene HcnsLTP111 positively regulates drought and salt stress tolerance in kenaf (Hibiscus cannabinus L.) - Dengjie Luo; Rehmat Ullah; Renxue Li; Benxian Li; Caijin Wang; Jiao Yue; Jiao Pan; Huaming Lu; Yun Li; Gang Jin; Ru Li; Tao Chen; et al. (Phytochemistry, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Influence of ambient wind on temperature distribution and smoke propagation in urban road tunnels with vertical shafts during fires - Peng Wu; Zhonghao Wen; Hongzhe Zhong; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2025)

Numerical simulations and theoretical analysis of ambient wind impact on shaft smoke exhaust performance in tunnel fires - Peng Wu; Junwei Chi; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Recent review on innovative strategies for enhancing the evaporation performance of 3D solar evaporator - Ru Song; Yanlong Shi; Ningshuang Zhang; Peng Wang; Shiyou Li (Journal of Environmental Chemical Engineering, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

Single-cell RNA sequencing of neonatal cortical astrocytes reveals versatile cell clusters during astrocyte-neuron conversion - Jiaxue Cha; Peng Zeng; Hui Zong; Jiayi Zhao; Jiayao Chen; Haowei Zuo; Bowen Zhang; Changjie Shi; Jing Li; Qiuhong Hua; Zixin Wang; Yujun Hou; et al. (Molecular Biology Reports, 2025)

Mechanistic insights into aristolochic acid-induced hepatocellular carcinoma: a multi-dimensional analysis integrating network toxicology, machine learning, and molecular dynamics simulation - Can Liu; Ru Qiao; Peng He; Wang Chen; Xiangting Gao; Fuyuan He (Toxicon, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

CaCl2 alleviates water-soaking disorder by attenuating mitochondrial oxidative damage in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Multi-omics insights into micro-oxygen-regulated microbial decolorization and metabolic pathways during hydrolysis and acidification of textile wastewater - Jiehui Ren; Qian Peng; Zhejun Du; Xiaoxin Yang; Jiayao Hui; Ru Li; Wen Cheng (Journal of Cleaner Production, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

LsMYB44 and LsWRKY75 regulate phenolic accumulation in fresh-cut stem lettuce treated with γ-aminobutyric acid (GABA) - Xueyin Ru; Jinglin Zhang; Wanli You; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Effect of exogenous DNP and ATP on storage quality, endogenous energy status and phenolic biosynthesis of shredded cucumber - Wanli You; Yiting Chen; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Journal of Stored Products Research, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

Efficient removal of dissolved tri-n-butyl phosphate from aqueous solution by immobilized bacterial microspheres - Si-Yi Ren; Zhao-Xing Peng; Jin-Ru Feng; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

The sprouting angiogenesis and vascular dysfunction triggered by bisphenol S and tetrabromobisphenol S through disrupting vascular endothelial-cadherin in zebrafish - Hongyuan Peng; Zehui Du; Jiali Li; Weiwei Wang; Ze Li; Shaoguo Ru (Environmental Research, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Comprehensive molecular biology and metabolomics analysis reveal the changes on muscle quality of Megalobrama amblycephala exposure to ammonia nitrogen during transportation - Ling Peng; Ziaur Rahman; Yuanyong Tian; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Lan Wang; Qilin Huang; Huawei Ma (Food Research International, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Zirconium phosphate nanonetworks for enhanced soft tissue integration and antibacterial performance of zirconia implant abutments - Yingyue Sun; Qihong Zhang; Shuyi Wu; Kendrick Hii Ru Yie; Lei Cai; Yinyan Zhang; Wen Si; Huan Cheng; Zijian Zheng; Peng Gao; Jinsong Liu; Lei Lu (Chemical Engineering Journal, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Differential analysis of microorganisms and flavor substances during drying of scallops (Chlamys farreri) based on high-throughput sequencing and headspace gas chromatography-mass spectrometry (HS-GC-MS) - Jing-ru Chen; Jia-bo Huang; Shi-meng Sun; Peng-fei Jiang (Food Bioscience, 2025)

Superior ammonia nitrogen adsorption capacity and reusability biochar microsphere applied in live fish transportation - Ling Peng; Tao Yin; Zhiyong Song; Shanbai Xiong; Ru Liu; Juan You; Qiling Huang (Chemical Engineering Journal, 2025)

High-performance multi-particle color electrophoretic display: A novel dual-charged particle strategy - Yue Zhang; Debo Zeng; Junjie He; Hailiang Sheng; Tao Zhou; Jintao Shi; Lisha Peng; Xinzao Wu; Bo-Ru Yang (Chemical Engineering Journal, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Low lipid levels caused by bisphenol S exposure trigger neuroinflammation and apoptosis in the brain of zebrafish - Zehui Du; Shuai Li; Hongyuan Peng; Jiali Li; Ze Li; Shaoguo Ru; Weiwei Wang (Aquatic Toxicology, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Correction: Ecological Environmental Changes and the Impact on Alpine Wetland Spatiotemporal Differentiation in Western Sichuan - Haijun Wang; Xiangdong Kong; Cuicui Jiao; Hu Li; Minghong Peng; Ji Luo; Onanong Phewnil; Ru Xue (Wetlands, 2025)

A new and rigorous SPN theory – The concluding Part V: Completion of the numerical solution method for GSP3 equations - Yung-An Chao; Ru-Ying Tang; Ziyong Li; Lianghui Peng (Annals of Nuclear Energy, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Facile preparation of hydrophobic covalent organic framework-coated sponge for efficient oil/water separation - Xiang Lai; Quanmei Duan; Chang Ru; Xin Zhang; Hui Zhao; Can-Peng Li (Journal of Water Process Engineering, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Ecological Environmental Changes and the Impact on Alpine Wetland Spatiotemporal Differentiation in Western Sichuan - Haijun Wang; Xiangdong Kong; Cuicui Jiao; Hu Li; Minghong Peng; Ji Luo; Onanong Phewnil; Ru Xue (Wetlands, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Lower-dose vs high-dose oral bisphenol S action of lipid metabolism in liver of male SD rat via mediating different SREBP isoforms - Jiali Li; Hongyuan Peng; Shaoguo Ru; Bo Wang; Enping Su; Dehua Wu; Weiwei Wang (Environmental Pollution, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

γ-aminobutyric acid treatment inhibits browning and promotes storage quality by regulating reactive oxygen species and membrane lipid metabolism in fresh-cut stem lettuce - Xueyin Ru; Wanli You; Jinglin Zhang; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Effects of dielectric barrier discharge cold plasma treatment on quality maintenance, energy and γ-aminobutyric acid accumulation of fresh-cut carrots - Wanli You; Xianwei Meng; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Control, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Exogenous Glutathione Enhances Salt Tolerance in Kenaf by Mediating Modulation of Oxidative Stress Response and DNA Methylation - Shan Cao; Guowang Liang; Lixia Zhang; Jiao Pan; Ru Li; Peng Chen (Journal of Plant Growth Regulation, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Seed priming using different agents can alleviate salt stress in kenaf (Hibiscus cannabinus L.) by activating antioxidant system and related genes expression - Renxue Li; Dengjie Luo; Muzammal Rehman; Xin Li; Caijin Wang; Shan Cao; Guofeng Xu; Meng Wang; Canni Chen; Jingzhi Nie; Ru Li; Tao Chen; et al. (Physiology and Molecular Biology of Plants, 2024)

Conical corner method for morphological optimization of right-angle turning slopes in mining waste dumps and its engineering application - Xuewen Ru; Suping Peng; Wenfeng Du (Bulletin of Engineering Geology and the Environment, 2024)

Effects of melatonin on sperm quality, enzyme activity, antioxidant gene expression and fertility of cryopreserved bovine semen - Peng Niu; Fei Huang; Jie Wang; Jia-jia Suo; Jie-ru Wang; Di Fang; Chun-mei Han; Qing-hua Gao (Theriogenology, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Upgrading the industrial structure for optimizing water-energy-carbon nexus in regional trade network - Benshuo Zhu; Ru Guo; Yun-en Tang; Kaiming Peng; Xiangfeng Huang (Journal of Cleaner Production, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Evaluating signal bleaching of Al and Ti–Li centers in fluvio-lacustrine sediments of Datong, North China, and its implications for the volcanic eruption chronology - Hao Ji; Chun-Ru Liu; Wen-Peng Li; Chuan-Yi Wei; Bhupati Neupane; Gong-Ming Yin (Quaternary Geochronology, 2024)

A cyclic nucleotide-gated channel gene HcCNGC21 positively regulates salt and drought stress responses in kenaf (Hibiscus cannabinus L.) - Canni Chen; Qijing Wu; Jiao Yue; Xu Wang; Caijin Wang; Rujian Wei; Ru Li; Gang Jin; Tao Chen; Peng Chen (Plant Science, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Study on factors influencing carbon dioxide emissions and carbon peak heterogenous pathways in Chinese provinces - Runpu Liu; Yan Ru Fang; Shuan Peng; Nihed Benani; Xuefang Wu; Yushuo Chen; Tao Wang; Qimin Chai; Pingjian Yang (Journal of Environmental Management, 2024)

Antioxidant properties and L-asparaginase activities of endophytic fungi from Cymbidium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Folia Microbiologica, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Melatonin improves cold storage tolerance in cucumber via CsMYB44-mediated transcriptional activation of the polyamine biosynthesis gene family - Miilion Paulos Madebo; Syed Umar Farooq Bokhary; Wanli You; Yinqiu Bao; Xueyin Ru; Yonghua Zheng; Peng Jin (Postharvest Biology and Technology, 2024)

Exogenous CaCl2 delays flesh softening by inhibiting the degradation of cell wall in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Exogenous chlorogenic acid inhibits quality deterioration in fresh-cut potato slices - Wanli You; Chunfei Wang; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Colonization ability and uniformity of resources and environmental factors determine biological homogenization of soil protists in human land‐use systems - Zhi‐Peng Li; Hua‐Yuan Shangguan; Haifeng Yao; Xiao‐Ru Yang; Yuri Mazei; Biao Zhu; Stefan Scheu; Xin Sun (Global Change Biology, 2024)
Humans have substantially transformed the global land surface, resulting in the decline in variation in biotic communities across scales, a phenomenon known as “biological homogenization.” However, different biota are affected by biological homogenization to varying degrees, but this variation and the underlying mechanisms remain little studied, particularly in soil systems. To address this topic, we used metabarcoding to investigate the biogeography of soil protists and their prey/hosts (prokaryotes, fungi, and meso‐ and macrofauna) in three human land‐use ecosystem types (farmlands, residential areas, and parks) and natural forest ecosystems across subtropical and temperate regions in China. Our results showed that the degree of community homogenization largely differed between taxa and functional groups of soil protists, and was strongly and positively linked to their colonization ability of human land‐use systems. Removal analysis showed that the introduction of widespread, generalist taxa (OTUs, operational taxonomic units) rather than the loss of narrow‐ranged, specialist OTUs was the major cause of biological homogenization. This increase in generalist OTUs seemingly alleviated the negative impact of land use on specialist taxa, but carried the risk of losing functional diversity. Finally, homogenization of prey/host biota and environmental conditions were also important drivers of biological homogenization in human land‐use systems, with their importance being more pronounced in phagotrophic than parasitic and phototrophic protists. Overall, our study showed that the variation in biological homogenization strongly depends on the colonization ability of taxa in human land‐use systems, but is also affected by the homogenization of resources and environmental conditions. Importantly, biological homogenization is not the major cause of the decline in the diversity of soil protists, and conservation and study efforts should target at taxa highly sensitive to local extinction, such as parasites.

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Glutamate application maintains quality and antioxidant capacity of fresh-cut carrots by modulating GABA shunt, phenylpropanoid and ROS metabolism - Jinglin Zhang; Jing Zhao; Xiaoxia Zuo; Wanli You; Xueyin Ru; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Potential use of maize–peanut intercropping to adapt to drought and nitrogen–shortage impacts - Fei Han; Shuqing Guo; Muhammad Asad Naseer; Ru Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Dong Yang; XiaoLi Chen; Xiaolong Ren (Plant and Soil, 2024)

DNA Methylome Provide New Insights into the Physiological-Molecular Regulation of Salt Stress in Kenaf Using 5-azaC Pretreatment - Zengqiang Li; Dengjie Luo; Shan Cao; Samavia Mubeen; Muzammal Rehman; Caijin Wang; Gang Jin; Ru Li; Tao Chen; Peng Chen (Journal of Soil Science and Plant Nutrition, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Initiation and Propagation of Interface Cracks in Layered Composite Rocks: An Investigation Using True Triaxial Experiments - Jian-Zhi Zhang; Tian-Tian Gu; Ru-Fang Zhan; Zhao-Peng Zhang (Geotechnical and Geological Engineering, 2024)

Identification of a Clinical Spirometra mansoni Plerocercoid Isolate Using Molecular and Morphological Data - Si Si Ru; Chi Cheng; Peng Jiang; Xi Zhang (Acta Parasitologica, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Assessing climate/air quality synergies and cost-effectiveness for Beijing transportation: Insights into sustainable development - Xuefang Wu; Roy M. Harrison; Min Chen; Tao Wang; Ruihe Lyu; Shuan Peng; Runpu Liu; Yushuo Chen; Yan Ru Fang; Pingjian Yang (Sustainable Cities and Society, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Seismic hazard models for typical urban masonry structures considering optimized regression algorithms - Si-Qi Li; Yi-Ru Li; Jia-Cheng Han; Peng-Fei Qin; Ke Du (Bulletin of Earthquake Engineering, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Calcium chloride treatment maintains quality and enhances antioxidant capacity of fresh-cut carrots through modulating DcCMLs-DcCAMTA3-mediated phenylpropanoid pathway - Jinglin Zhang; Xiaoxia Zuo; Yanfei Li; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Physiological, transcriptome and gene functional analysis provide novel sights into cadmium accumulation and tolerance mechanisms in kenaf - Shan Cao; Meng Wang; Jiao Pan; Dengjie Luo; Samavia Mubeen; Caijin Wang; Jiao Yue; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Journal of Environmental Sciences, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Integrated straw-derived biochar utilization to increase net ecosystem carbon budget and economic benefit and reduce the environmental footprint - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Morpho-physio-biochemical, molecular, and phytoremedial responses of plants to red, blue, and green light: a review - Muzammal Rehman; Jiao Pan; Samavia Mubeen; Wenyue Ma; Dengjie Luo; Shan Cao; Wajid Saeed; Gang Jin; Ru Li; Tao Chen; Peng Chen (Environmental Science and Pollution Research, 2024)

Addressing the influencing path of social noise exposure risk perception on noise mitigation behavior - Chunyan Wang; Yihan Li; Yayun Shen; Yi Liu; Peng Ru; Zeyang Wei; Dan Xie (Journal of Environmental Management, 2024)

Maize/peanut rotation intercropping improves ecosystem carbon budget and economic benefits in the dry farming regions of China - Fei Han; Talha Javed; Sadam Hussain; Shuqing Guo; Ru Guo; Lihua Yang; Xiantong Liu; Tie Cai; Peng Zhang; Zhikuan Jia; Anis Ali Shah; Xiaoli Chen; et al. (Journal of Environmental Management, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Waterlogging influences the physiology index and antioxidant enzyme activity in Cucurbita maxima and Cucurbita moschata - Kuan-Hung Lin; Shi-Peng Chen; Yi-Ru Su; Yi-Heng Tsai; Hsin-Hung Lin (Horticulture, Environment, and Biotechnology, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

CaCl2 promoted phenolics accumulation via the CmCAMTA4-mediated transcriptional activation of phenylpropane pathway and energy metabolism in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Insights into greenhouse gas emissions from a wastewater treatment plant in vulnerable water areas of China - Jiemiao Ma; Xiaojing Ni; Chen Cai; Yuewu Da; Kan Hu; Ru Guo; Jia Liu; Kaiming Peng; Erwu Liu; Xiangfeng Huang (Science of The Total Environment, 2023)

Topology optimization on periodic pile barriers considering material damping based on complex band diagrams - Peng Zhou; Shui Wan; Xiao Wang; Aiming Song; Ru Yue (Computers and Geotechnics, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Characterization and antimicrobial activities of bioactive compounds from endophytic Trichoderma asperellum isolated from Dendrobium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Biologia, 2023)

A hybrid piezoelectric-electromagnetic energy harvester used for harvesting and detecting on the road - Laihu Peng; Yi Wang; Yubao Qi; Xin Ru; Xudong Hu (Journal of Cleaner Production, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Exogenous glutathione can alleviate chromium toxicity in kenaf by activating antioxidant system and regulating DNA methylation - Meiqiong Tang; Ru Li; Peng Chen (Chemosphere, 2023)

The interaction between DcCaM7 and DcCAMTA6 promotes γ-aminobutyric acid (GABA) accumulation via regulating GABA shunt in fresh-cut carrots - Jinglin Zhang; Yanfei Li; Xiaoxia Zuo; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Comparative analysis of antimicrobial compounds from endophytic Buergenerula spartinae from orchid - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Antonie van Leeuwenhoek, 2023)

Functional characterization of African swine fever virus I329L gene by transcriptome analysis - Xianghan Duan; Yuan Wen; Panxue Wu; Jiangling Peng; Yanlong Zhou; Guoqiang Zhu; Dan Li; Yi Ru; Wenping Yang; Haixue Zheng (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Targeting STING-mediated pro-inflammatory and pro-fibrotic effects of alveolar macrophages and fibroblasts blunts silicosis caused by silica particles - Liang Ou; Peng Zhang; Zhengpeng Huang; Yuxing Cheng; Qianru Miao; Ru Niu; Yuxin Hu; Ying Chen (Journal of Hazardous Materials, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

PpMYB44 positively affects salicylic acid biosynthesis in Pichia guilliermondii-induced peach fruit resistance against Rhizopus stolonifer - Yanfei Li; Jinglin Zhang; Nana Ji; Xiaoxia Zuo; Xueyin Ru; Peng Jin; Kaituo Wang; Yonghua Zheng (Postharvest Biology and Technology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Physiological and DNA methylation analysis provides epigenetic insights into kenaf cadmium tolerance heterosis - Dengjie Luo; Hai Lu; Caijin Wang; Samavia Mubeen; Shan Cao; Jiao Yue; Jiao Pan; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Plant Science, 2023)

Polysaccharides from the hard shells of Juglans regia L. modulate intestinal function and gut microbiota in vivo - Xiaoyu Li; Siying An; Zhen Luo; Peng Zhou; Lu Wang; Ru Feng (Food Chemistry, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

NOS2/miR-493-5p Signaling Regulates in the LPS-Induced Inflammatory Response in the RAW264.7 Cells - Xiaofei Li; Yongrui Yang; Nihong Lu; Feng Luo; Ru Fan; Niancai Peng (Biochemical Genetics, 2023)

Long-term straw incorporation regulates greenhouse gas emissions from biodegradable film farmland, improves ecosystem carbon budget and sustainable maize productivity - Rui Qian; Ru Guo; Muhammad Asad Naseer; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

Rotation of planting strips and reduction in nitrogen fertilizer application can reduce nitrogen loss and optimize its balance in maize–peanut intercropping - Fei Han; Ru Guo; Sadam Hussain; Shuqing Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Muhammad Asad Naseer; Muhammad Saqib; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2023)

Organic fertilizer substitution promotes soil organic carbon sequestration by regulating permanganate oxidizable carbon fractions transformation in oasis wheat fields - Hao He; Mengwen Peng; Weidan Lu; Sibo Ru; Zhenan Hou; Junhua Li (CATENA, 2023)

Identification of mercury species in coal combustion by-products from power plants using thermal desorption-atomic fluorescence spectrometry on-line coupling system - Kai-Qiang He; Xiao-Ru Zhang; Yuan-Peng Li; Xue-Lei Duan; Yan Li; Yang-Hong Jiang; Xiao-Dong Yuan; Ke-Gang Zhang; Chun-Gang Yuan (Chemosphere, 2023)

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Dynamic roles of inner membrane electron-transfer hub of Shewanella oneidensis MR-1 in response to extracellular reduction kinetics - Xiang Xiao; Chang-Xing Li; Jie-Ru Peng; Yang-Yang Fan; Wen-Wei Li (Chemical Engineering Journal, 2023)

Differences in drought evolution as portrayed for China using various evapotranspiration models and drought indices - Huaijun Wang; Lei Cao; Xinchuan Li; Ru Feng; Peng Zheng (International Journal of Climatology, 2022)
Drought, a slow‐growing natural disaster that affects large areas worldwide, has serious social and economic consequences. There is compelling evidence to suggest that drought will be more prevalent in various regions in the future, due to the impact of climate change. Evapotranspiration is an important drought evolution control factor, and various evapotranspiration models show different drought evolution trends. In the study described here, meteorological data from 840 Chinese weather stations, for 1960–2018, were used to estimate potential evapotranspiration (PET), using the Thomthwaite (TH), Hargreaves (HG), Priestley–Taylor (PT), Penman and Penman–Monteith (PM) models. We then compared various drought indices (the standardized precipitation index [SPI], the standardized precipitation evapotranspiration index [SPEI], and the Palmer drought severity index [PDSI]), calculated using inputs from the five evapotranspiration models. The results showed that (a) evapotranspiration means and trends, as estimated by the five PET models, were significantly different, with Penman giving the highest estimate while TH the lowest. Differences between the PET model outcomes reduced under climate warming scenarios; (b) significantly different evapotranspiration models and drought indices can give rise to varied results, with the climate becoming wetter under the Penman and PM models (especially in western northwest China and eastern south China), and drier under the TH model; (c) the different drought forecasts obtained using the evapotranspiration models decreased with increasing precipitation, for all regions; (d) the SPEI is more suitable for drought monitoring compared with PDSI due to the higher sensitive to the choice of evapotranspiration model of SPEI; and (e) SPEI‐PM and SPEI‐Penman is the best drought indices in all regions. SPEI‐PT and SPEI‐HG can be applied in regions with relatively abundant precipitation (northern north China, southern north China, eastern south China, western south China, and Tibetan Plateau), and SPEI‐PM and SPEI‐Penman can be suitable for drought monitoring in arid and semi‐arid regions (western northwest China and eastern northwest China). The results presented herein are expected to aid in the selection of a proper drought index for disaster assessment.

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Increase in rosmarinic acid accumulation and transcriptional responses of synthetic genes in hairy root cultures of Prunella vulgaris induced by methyl jasmonate - Mei Ru; Yonghua Li; Min Guo; Liuyan Chen; Yong Tan; Liang Peng; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

First report of Cytospora chrysosperma causing canker on staghorn sumac in China - Zhe Wang; Hai-ting Hao; Shuai-shuai Sha; Sha-sha Peng; Xin-ru Zhang; Lan Wang; Hong-zu Feng (Journal of Plant Pathology, 2022)

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

A comprehensive integrated transcriptome and metabolome analyses to reveal key genes and essential metabolic pathways involved in CMS in kenaf - Meiqiong Tang; Zengqiang Li; Dengjie Luo; Fan Wei; Muhammad Haneef Kashif; Hai Lu; Yali Hu; Jiao Yue; Zhen Huang; Wenye Tan; Ru Li; Peng Chen (Plant Cell Reports, 2021)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Thalamocortical dysconnectivity in premenstrual syndrome - Peng Liu; Ying Wei; Hai Liao; Yingying Fan; Ru Li; Nana Feng; Gaoxiong Duan; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2019)

Study on the Mechanical Properties and Mechanical Response of Coal Mining at 1000 m or Deeper - Heping Xie; Mingzhong Gao; Ru Zhang; Gaoyou Peng; Wenyong Wang; Anqiang Li (Rock Mechanics and Rock Engineering, 2019)

Andrographolide impairs alpha-naphthylisothiocyanate-induced cholestatic liver injury in vivo - Lei Wang; Fei Cao; Li-li Zhu; Peng Liu; Yu-ru Shang; Wen-hui Liu; Xin Dong; Hai-dong Bao; Peng Gong; Zhong-yu Wang (Journal of Natural Medicines, 2019)

Dispersion and attenuation of compressional waves in tight oil reservoirs: Experiments and simulations - Ru-Peng Ma; Jing Ba; José Maria Carcione; Xin Zhou; Fan Li (Applied Geophysics, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Chloroplast genome sequence of an endangered non-photosynthetic mycoheterotrophic species Monotropastrum sciaphilum (Andres) G. D. Wallace - Qian-Ru Zhao; Zhen-Wen Liu; Chao Shi; Hua Peng; Shu-Gang Lu (Conservation Genetics Resources, 2018)

Altered topological patterns of brain functional networks in Crohn’s disease - Peng Liu; Ru Li; Chunhui Bao; Ying Wei; Yingying Fan; Yanfei Liu; Geliang Wang; Huangan Wu; Wei Qin (Brain Imaging and Behavior, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Ectopic expression of sorbitol-6-phosphate 2-dehydrogenase gene from Haloarcula marismortui enhances salt tolerance in transgenic Arabidopsis thaliana - Jian-jie Gao; Yu-ru Sun; Bo Zhu; Ri-He Peng; Bo Wang; Li-Juan Wang; Zhen-Jun Li; Lei Chen; Quan-Hong Yao (Acta Physiologiae Plantarum, 2018)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Activation of liver X receptor α protects amyloid β1–40 induced inflammatory and senescent responses in human retinal pigment epithelial cells - Bingling Dai; Chunyan Lei; Ru Lin; Lifei Tao; Yue Bin; Hui Peng; Bo Lei (Inflammation Research, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Molecular cloning and characterisation of two enzymes involved in the rosmarinic acid biosynthesis pathway of Prunella vulgaris L. - Mei Ru; Kunru Wang; Zhenqing Bai; Liang Peng; Shaoxuan He; Tianlin Pei; Yanyan Jia; Hongyan Li; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Establishment of Salvia castanea Diels f. tomentosa Stib. hairy root cultures and the promotion of tanshinone accumulation and gene expression with Ag+, methyl jasmonate, and yeast extract elicitation - Bo Li; Bangqing Wang; Hongyan Li; Liang Peng; Mei Ru; Zongsuo Liang; Xijun Yan; Yonghong Zhu (Protoplasma, 2016)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

Etanercept in the Treatment of Intestinal Behcet’s Disease - Dan Ma; Chao-Jun Zhang; Ru-Peng Wang; Lie Wang; Hua Yang (Cell Biochemistry and Biophysics, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Origin of Early Cretaceous high-K calc-alkaline granitoids, western Tibet: implications for the evolution of the Tethys in NW China - Yao-Hui Jiang; Zheng Liu; Ru-Ya Jia; Shi-Yong Liao; Peng Zhao; Qing Zhou (International Geology Review, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Classifying human operator functional state based on electrophysiological and performance measures and fuzzy clustering method - Jian-Hua Zhang; Xiao-Di Peng; Hua Liu; Jörg Raisch; Ru-Bin Wang (Cognitive Neurodynamics, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

(−)-Epigallocatechin-3-gallate alleviates spatial memory impairment in APP/PS1 mice by restoring IRS-1 signaling defects in the hippocampus - Ning Jia; Kun Han; Jing-Jing Kong; Xiu-Mei Zhang; Sha Sha; Gui-Ru Ren; Yun-Peng Cao (Molecular and Cellular Biochemistry, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Petrogenesis and tectonic implications of early Silurian high-K calc-alkaline granites and their potassic microgranular enclaves, western Kunlun orogen, NW Tibetan Plateau - Ru-Ya Jia; Yao-Hui Jiang; Zheng Liu; Peng Zhao; Qing Zhou (International Geology Review, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Characterisation of Ilomastat for Prolonged Ocular Drug Release - Gary Parkinson; Simon Gaisford; Qian Ru; Alastair Lockwood; Ashkan Khalili; Rose Sheridan; Peng T. Khaw; Steve Brocchini; Hala M. Fadda (AAPS PharmSciTech, 2012)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

A Role of the Mammalian Target of Rapamycin (mTOR) in Glutamate-Induced Down-regulation of Tuberous Sclerosis Complex Proteins 2 (TSC2) - Wenjuan Ru; Yanxi Peng; Ling Zhong; Shao-Jun Tang (Journal of Molecular Neuroscience, 2012)

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China - Ru Cheng Wang; A-Peng Yu; Jun Chen; Lei Xie; Jian-Jun Lu; Jin-Chu Zhu (Mineralogy and Petrology, 2012)

Expression of tyrosine kinase receptor C in the segments of the spinal cord and the cerebral cortex after cord transection in adult rats - Dong-Xiang Qian; Hong-Tian Zhang; Ying-Qian Cai; Peng Luo; Ru-Xiang Xu (Neuroscience Bulletin, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Cloning and characterization of novel low molecular weight glutenin subunit genes from two Aegilops species with the C and D genomes - Peng Chen; Ru Li; Ruiyang Zhou; Zhiguo E; Guangyuan He (Genetic Resources and Crop Evolution, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Maternal lineages of Pinus densata , a diploid hybrid - Bao‐Hua Song; Xiao‐Quan Wang; Xiao‐Ru Wang; Lan‐Ju Sun; De‐Yuan Hong; Pei‐Hao Peng (Molecular Ecology, 2002)
Previous morphological, allozyme and chloroplast DNA data have suggested that Pinus densata originated through hybridization between P . tabuliformi s and P . yunnanensis . In the present study, sequence and restriction site analyses of maternally inherited mitochondrial nad 1 intron were used to detect variation patterns in 19 populations of P . tabuliformis , P . yunnanensis and P . densata . A total of three mitotypes (A, B, C) were detected. All but one of the populations of P . yunnanensis possessed mitotype B while all populations of P . tabuliformis had mitotype A. Pinus densata populations, on the other hand, harboured both mitotypes A and B, which are characteristic of P . tabuliformis and P . yunnanensis , respectively . This result gives strong additional evidence supporting the hybrid origin of this diploid pine. The distribution of mitotypes indicated very different mating compositions and evolutionary history among P . densata populations. It seems that local founder populations and backcrosses may have played important roles in the early establishment of P . densata populations. The uplift of the Tibetan Plateau had a significant impact on the distribution of maternal lineages of P . densata populations.

Seismic depth migration with pseudo-screen propagator - Shengwen Jin; Ru-Shan Wu; Chengbin Peng (Computational Geosciences, 1999)